ELECTROSPUN NANOFIBER FROM STYROFOAM WASTE FOR AIR FILTRATION APPLICATION - Rajak, Abdul
This disertation reports on the recycling of styrofoam (expanded polystyrene (EPS)) waste to be nanofibrous mats for air filtration application. The styrofoam nanofibrous mats were synthesized via electrospinning technique. The EPS solutions for producing the mats were made by dissolving the styrofoam waste in the mixing of dimethylformamide (DMF) and d-limonene as solvents. The fiber diameter ranges obtained in study were and 314 - 3,506 nm. In the range those fiber diameter, different fiber morphology was found ie. smooth fiber, wrinkled fiber, and beaded fiber. The synthesized EPS nanofibrous mats were characterized by scanning electron microscope (SEM), Fourier-transform infrared (FTIR) spectroscopy, x-ray diffraction (XRD) spectroscopy, differential scanning calorimetry (DSC), mechanical strength, porosity, and water contact angle measurement apparatus. The mechanical strength measurement exhibited that the beaded fiber has the highest tensile strength and the lowest elasticity compared to wrinkled and smooth fiber. The water contact angle measurement showed that the EPS nanofibrous mats were classified into hydrophobic, ultra-hydrophobic and super-hydrophobic with the contact angle value of 106, 127 and 153o, respectively. Some filtration parameters of the EPS nanofibrous mats were measured, including particle collecting efficiency, pressured drop, and quality factor. The particle collecting efficiency of each EPS nanofibrous mats was measured using monodisperse polystyrene latex (PSL) particles and PM2.5 from burning incense as the test particles. The EPS nanofibrous mats had a high collecting efficiency (up to 99.99%) and had a low pressure drop (below 70 Pa) for the face velocity of 5.4 cm s-1. The quality factor of the EPS nanofibrous mats reached 0.10 for PSL filtration and 0.16 for PM2.5 filtration. Overall, the EPS nanofibrous mats with controlled morphology were suitable to be used as air filtration media.